Development of learning media Indonesian Web-Based platform using Google Sites - Wahyudi Wahyudi; Ahadi Sulissusiawan; Patriantoro Patriantoro; Hotma Simanjuntak; Sesilia Seli (Institute of Computer Science (IOCS), 2023)
The Indonesian language learning paradigm shifted after the Covid-19 outbreak. The lack of learning media that can handle all learning material and instructors' poor mastery of technology both contribute to this problem. Building a web-based learning platform using Google Sites and the data from the Observation Report Text is one solution to this problem. The study's goals are to create a procedure for developing learning media on a web platform, to establish whether or not such media is feasible, and to identify the variables enabling and limiting the use of Google Sites. R&D (Research & Development) development principles and the ADDIE model inform the study's methodology. Twenty-one kids were randomly selected from Grade X at IPS SMA Pelita Cemerlang Pontianak. Methods of gathering information include keeping records, conducting surveys, and keeping careful notes. The media professionals who checked out https://sites.google.com/bindoxpelitacemerlang gave it an 82.44%. The validation by subject matter experts is at 96.97%, while the validation by end users is at 88.9%; both scores place the material in the 'Very Eligible' category. Black-box testing tools, stress testing, installation/lauch testing, alpha testing, and 'passing' beta testing are used to determine Google Sites' viability. High accessibility, students' ability to study independently, opening links, dynamic time, extra learning resources, information search columns, and readily updatable content and materials are all reasons to use Google Sites. There are several limitations, such as a lack of personalization, the need for an active internet connection, concerns about privacy and security, and the presence of broken connections.